Determination of vitamin D level in chicken eggs from conventional and free range systems - Gul, Burcu; Yerebasan, Ulku; Baygeldi, Yavuz; Korkak, Fatih Ahmet; Baykalir, Yasin (Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA, 2023)
This study aimed to investigate the vitamin D levels and some quality features of eggs. A total of 150 eggs (75 conventional and 75 free-range) were selected for the study. The levels of 25-OH vitamin D were determined by liquid chromatography with tandem mass spectrometry (LC-MS/MS) in egg yolks. Furthermore, we evaluated the weights of egg, yolk, albumen, and yolk color as well as shape index, shell thickness, and percentages of albumen, yolk, and shell. The 25-OH vitamin D levels were significantly higher (P < 0.01) in the conventional than in the free-range eggs. Furthermore, the weights of egg, albumen, yolk, percentage of yolk and yolk color were significantly higher (P < 0.01) in the conventional than in the free-range eggs. However, the shape index, percentage of albumen, percentage of shell and shell thickness were significantly higher (P < 0.01) in the free-range than the conventional eggs. It can be concluded that vitamin D levels in eggs can be related to yolk color. However, egg quality characteristics can also be influenced by various environmental factors. © 2023, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved.
Keywords: chicken; egg quality; rearing systems; vitamin D